Experimental and theoretical studies on pyrene-grafted polyoxometalate hybrid - Chen, Hongyu (2013)
A novel pyrene covalently-attached polyoxometalate (POM) hybrid has been synthesized and fully characterized. The attractive electronic and photophysical properties of pyrene derivatives make the hybrid promising for studying and understanding electron transfer mechanisms in organic-functionalized POMs. The hybrid has an electronic absorption at 450 nm, indicating that there is a strong electronic interaction between the organic pyreneimido group and inorganic hexamolybdate cluster. The electron transfer mechanism of the as-prepared hybrid is illuminated via the combined studies of theoretical calculations and transient absorption spectroscopy. Time-dependent density functional theory studies revealed that the strong electronic absorption at the visible region mainly comes from the optically allowed π–π* transitions of the pyreneimido component (S0 to S2 transition). The electron transfer process from the excited pyreneimido moiety to the inorganic POM cluster is at the time scale of [similar]700 fs, which could be ascribed to the internal conversion of singlet excited states from S2 state to S1 state. This study provided a clear understanding of the mechanism governing the electron transfer process in organoimido derivatives of POMs. This result might offer a new route for the design of new charge transfer hybrid clusters of organic functionalized POMs and crucial guidance for their applications in optical and electrical devices.